PELAKSANAAN PROMOSI KESEHATAN RUMAH SAKIT DI RSJD DR. AMINO GONDOHUTOMO PROVINSI JAWA TENGAH - Besar Tirto Husodo; Bagoes Widjanarko; Alifia Ardyara (Jurnal Kesehatan Masyarakat (Undip), 2017)
In Indonesia, the most severe mental disorders in 2013 are in Yogyakarta, Aceh, Bali, South Sulawesi and Central Java. In 2016 at psychiatric hospital RSJD. Dr. Amino Gondohutomo, mentally rehabilitated patient (readmission) of 204 clients showing an increase from 2015 to 179 clients. The family function as a health care, recurrence can be prevented if the family can recognize problems experienced by his family. Hospital Health Promotion (PKRS) plays a role in channeling information to patients, families of patients, and clients as healthy prevention. The purpose of this research is to see the implementation of PKRS unit according to success indicator of Hospital Health Promotion Technical Directive from the Ministry of Health 2014. This research is a qualitative research with descriptive approach. Data collection was done by indepth interview. The main informants are 3 people who are the staff of PKRS team. The triangulation informant is 8 persons who are the staff of RSJD Dr. Amino Gondohutomo Central Java Province, family of outpatient patients, and drug rehabilitation patients. From the result of the research, it is known that PKRS team management is still double job with the main profession and there is no special training of health promotion, limited facilities and media provision to adjust the fund, the process of counseling in waiting room has not been routine, is doing Desa Siaga Sehat Jiwa creation, Can design the media, PKRS covers all parts of the hospital but there is no monitoring evaluation per section, there is no target success of the number of patients receiving PKRS services. So that, the need for training for PKRS members so that the implementation of PKRS in RSJD Dr. Amino Gondohutomo Central Java Province become effective and efficient.